Envisioning scientific innovation in Korea's demilitarized zone : a step toward economic progress and global peace - Yoon, Jong-Lok (2020)
Ongoing progress in inter-Korea relations suggests that a new era of peace could soon emerge on the Korean Peninsula. There is renewed hope for scientific cooperation between the two Koreas, along with broader engagements with other stakeholders. Key needs include managing the region’s biodiversity and fostering economic progress with an eye toward potential unification. Herein, we introduce current efforts to preserve the biodiversity of the Demilitarized Zone (DMZ) through conservation efforts, while discussing how the DMZ question highlights a broader need to promote scientific innovation and economic development through mutual cooperation. Using the DMZ as an example, we discuss how sustainable natural resources, such as pollen grains present there, might serve as a catalyst to promote scientific cooperation, foster high-tech innovation, and generate economic impact. Looking forward, such efforts will hopefully lead to a bright future on the Korean Peninsula and global peace.